1999
DOI: 10.1093/humrep/14.5.1262
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of in-vitro fertilization through natural cycles in poor responders

Abstract: This prospective study examines the benefits of using natural cycles instead of stimulated cycles in poor responders to in-vitro fertilization (IVF) treatment. Eleven patients in whom puncture was cancelled or who failed to conceive because of a poor response were included in the analysis. The data for natural cycles (n = 16) were compared with data obtained during previous stimulated cycles (n = 25) in the same women. Out of 16 natural cycles, 13 (81.3%) were scheduled for oocyte retrieval compared to 13 out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 20 publications
5
27
0
12
Order By: Relevance
“…Women aged >40 years of poor ovarian response can be considered to have donor oocytes or to undergo natural IVF cycle. Natural IVF cycle without/with minimal stimulation can be considered as an easy and cheap approach in the management of poor responder patients [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Women aged >40 years of poor ovarian response can be considered to have donor oocytes or to undergo natural IVF cycle. Natural IVF cycle without/with minimal stimulation can be considered as an easy and cheap approach in the management of poor responder patients [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The results of two prospective studies [171,178] support the hypothesis that the naturally developed follicles of poor responders may produce fewer oocytes but oocytes of better quality than their hyperstimulated ovaries. It is clear that, in poor responders, natural cycle is superior once an oocyte has been retrieved and fertilization and implantation rates are significantly better.…”
Section: Gnrh Antagonists Regimens (Gnrh-ant)mentioning
confidence: 73%
“…In a review by Pelenck and collegues [170], the cancellation rate in natural cycles was reported to range from 14.3 to 62.5%. Natural cycles in IVF have been used for patients who have shown a poor response in at least two previous attempts with gonadotropin stimulation [171]. It has been suggested in recent years that IVF following a natural cycle may be a promising alternative for poor responders [172].…”
Section: Gnrh Antagonists Regimens (Gnrh-ant)mentioning
confidence: 99%
“…Therefore there is an increasing desire for milder ovarian stimulation using either lower amounts of gonadotropins, or, ideally, dispensing with ovarian stimulation altogether [14]. An alternative approach is to use natural cycle IVF [15]. However, since there is generally only one preovulatory follicle in a natural cycle, many women will not have an oocyte collection or embryo transfer [15].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to use natural cycle IVF [15]. However, since there is generally only one preovulatory follicle in a natural cycle, many women will not have an oocyte collection or embryo transfer [15]. It has been shown that IVM is a successful method of treatment in women who have polycystic ovarian syndrome [3,7,16].…”
Section: Discussionmentioning
confidence: 99%